Analisis Hubungan Antar Parameter Air Bersih di Sekitar Rencana Pembangunan Pasar Agro Kabupaten Bojonegoro - Tri Karisma Wardhani; Okik Hendriyanto Cahyonugroho (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Markets are places that facilitate buying and selling activities and are visited by many people, it making them vulnerable to the spread of a disease that can come from virus-carrying animals or inadequate sanitation. A healthy market should have good sanitation, such as adequate availability of water as sanitary higiene with adequate quality. Water used for sanitary hygiene purposes must be protected from pollutant sources and safe from contamination, and meet quality standards according to Regulation of the Minister of Health No. 32 of 2017. Therefore, to determine the quality of water that will be used to meet the sanitation needs of the market, this study measured the quality of clean water directly at three points around the location of the “Pasar Agro” development plan. Water quality measurements are carried out using methods according to the Indonesian National Standard according to each parameter to be measured. Based on the results of the measurements carried out, there are two chemical parameters that have not met, namely manganese and detergent parameters, as well as biological parameters in the form of total coliform. Correlation testing was carried out using Minitab 17 software on water chemistry parameters to determine the relationship between parameters, and it was found that there were only a few parameters that were related to each other.